Argumentum Ornithologicum: How Avian Metaphors Help Understand Artistic Research Better - Aldis Gedutis; Vytautas Michelkevičius (Sociologija: Mintis ir Veiksmas, 2022)
The article aims to examine the phenomenon of artistic research in the broader context of sciences and arts. For that purpose, Pierre Bourdieu’s methodological principle ‘exoticize the domestic’ is used. This principle enables to change and alter the epistemic perspective suggesting that ordinary and everyday things should be investigated as if they were alien and strange. In place of theoretical arguments for and against artistic research, an avian metaphor is invoked, which enables to exoticize the domestic sufficiently. By continuing and expanding the existing avian metaphors, the article aims to highlight those aspects of artistic research that are not easy to grasp and distinguish with the help of the usual arguments pro and con artistic research. The main question to be answered: how does the perception of artistic research change when looking at it as a phenomenon of the ornithological world?